The Puzzling Practice of Paying "Cash for Votes" - Anand Murugesan; Jean-Robert Tyran (Center for Economic Studies and ifo Institute (CESifo), 2023)
The expression "cash-for-votes" describes a form of vote buying in which candidates for office pay individuals in exchange for their votes. That practice undermines the functioning of democracy but is pervasive in many parts of the world, especially in the Global South. We discuss estimates of cash-for-votes and rational choice theories to explain their existence. Cash-for-votes under secret ballots is puzzling as secret ballots make it impossible to verify an individual's vote. We discuss the behavioral and experimental literature emphasizing factors such as reciprocity, unsophisticated voting, and inequality aversion, which complement standard economic explanations of the phenomenon.
Keywords: D72; D73; K42; 330; democracy; vote buying; secret ballot; reciprocity